Feeding Eggs from Hens Immunized with Specific KLH-Conjugated HIV Peptide Candidate Vaccines to Chicks Induces Specific Anti-HIV gp120 and gp41 Antibodies that Neutralize the Original HIV Antigens - Justiz Vaillant; Ferrer Cosme; Fisher Smikle; Oliver Pérez (Vaccine Research, 2020)
Introduction: Isolation of antibodies from the egg yolk of chickens is of particular interest as a source of specific antibodies for oral administration to prevent infections and use them as immunodiagnostic reagents. This study assessed the hypothesis that immunization with human immunodeficiency virus 1(HIV-1) viral peptides could induce a potent immune response that could be evaluated in chicken eggs. Methods: Nine healthy brown Leghorn layer hens (3 per HIV immunogen), aged 7 months, were immunized intramuscularly at multiple sites on the breast with specific KLH-conjugated HIV peptide candidate vaccines. The anti-HIV antibody response was measured using ELISA. Chicks were fed HIV hyper-immune eggs and their blood was collected for testing for anti-anti-idiotypic antibodies that neutralize the original HIV antigen using an inhibition ELISA. Results: The immunogenicity results showed that HIV peptide vaccines effectively produced strong anti-HIV immune responses in immunized brown Leghorn layer hens. The binding inhibition assay showed that 13.9%–20.3% inhibition of the binding of avian anti-HIV gp 41 (fragment 579-601) or anti-HIV-gp120 antibodies (Ab-1) to immobilized HIVgp41, HIVgp120 peptide by anti-HIV gp 41 (fragment 579-601) or anti-HIV gp120 (fragments 308-331 or 421-438) antibodies present in serum sample replicates of chicks tested, suggesting that the chicks anti-HIV gp 41 (fragment 579-601) or anti-HIV-gp120 antibodies (fragments 308-331 or 421-438) were anti-anti-idiotypic antibodies. This inhibition was not observed in the sera of chicks that were not fed with the hyperimmune eggs. Conclusion: Feeding chicks with hyperimmune eggs could potentially stimulate the production of anti-anti-idiotypic antibodies that can neutralize the original HIV antigen (gp120 or gp41). This could be an avenue for immunotherapy to improve the fight against HIV infections. However, more studies and clinical trials are required to demonstrate similar human immune responses.